PERBEDAAN HASIL BELAJAR DAN AKTIVITAS SISWA YANG DIAJAR MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DENGAN MODEL KOOPERATIF TIPE SNOWBALL THROWING DI KELAS XI IPA SMA NEGERI 15 MEDAN - Nur Fatiha Utami; Mariaty Sipayung (Jurnal Pelita Pendidikan, 2017)
This research aims to investigate the difference of student learning outcomesandactivities between cooperative learning model Student Teams Achievement Divisions typeand cooperative model type Snowball Throwing in Human Reproduction System topic in classXI IPA SMA Negeri 15 Medan academic year 2015/2016. This research is an experimentalresearch. To obtain student learning outcome this research uses Test with design pretest andposttest and to obtain student learning activities this research uses Observation. The samplingtechnique used in this research is random sampling technique. The total number of samples is74 students. They are XI IPA2 was taught by applying cooperative learning model StudentTeams Achievement Division type and XI IPA3 was taught by applying Snowball Throwing type.The data of the research were analyzed by using ttest technique (two tails) with α = 0.05. Thedata shows that tcount activities = -4.33 and tcount leaning outcomes = -2.90, and both values arenot between ttable = -1.996 up to 1.996. It means that Ho is rejected. So, it can be concludedthat there are significant differences of student learning activities and outcomes betweencooperative model Student Teams Achievement Division type and Snowball Throwing type inHuman Reproduction System topic in class XI IPA SMA Negeri 15 Medan.Key words: Cooperative Learning Model, STAD, Snowball Throwing, Learning Outcomes,Learning Activities